Maine coon cats - Quasha, Jennifer (New York : PowerKids Press, 2000)
Relates the history of one of the oldest breeds of cats to develop in the United States and describes its physical and other characteristics.
Includes index.
Keywords: Maine coon cat -- Juvenile literature; Maine coon cat; Cats